2020
DOI: 10.1016/j.jcol.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Ostomy time and nutrition status were associated on quality of life in patients with colorectal cancer

Abstract: Introduction  Colorectal cancer frequency increases each year and consequently the number of ostomies, a procedure that helps in the treatment of colorectal cancer but has an impact on quality of life. Studies evaluating the impact of ostomy time and nutritional status on the quality of life of colostomized patients with colorectal cancer are scarce in the literature. So, the aim of this study was to evaluate the association ostomy time and nutritional status on quality of life in colostomized colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Chemotherapy, an essential component of cancer management comes with significant distress to patient at various stages of treatment plan [ 11 , 27 ]. Multiple studies have demonstrated that presence of stoma is associated with poor QOL [ 28 , 29 ]. Likewise our study shows that patients who had a stoma in their treatment plan had a significantly poor global QOL score.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy, an essential component of cancer management comes with significant distress to patient at various stages of treatment plan [ 11 , 27 ]. Multiple studies have demonstrated that presence of stoma is associated with poor QOL [ 28 , 29 ]. Likewise our study shows that patients who had a stoma in their treatment plan had a significantly poor global QOL score.…”
Section: Discussionmentioning
confidence: 99%
“…Given this need, it becomes essential to monitor the changes in eating habits that people with intestinal ostomies experience since nutrition influences bowel function and elimination, which can generate undesirable effects, such as the increase of flatus, associated with the stoma type (97,98), resulting in poorer quality of life, since the loss of consumption of certain foods may deprive the pleasurable sensations associated with eating (99,100).…”
Section: Discussionmentioning
confidence: 99%
“…As orientações dos profissionais ajudam no manejo da bolsa de colostomia, pois os pacientes têm relevante dificuldade quanto a isso, o que leva a convivência a ser um óbice que deve ser constantemente enfrentado. Estas orientações possibilitam aos ostomizados cuidar com confiança e segurança, melhorando sua qualidade de vida, exercida sob seu autocuidado, o que evita complicações, além de se aceitar e conduzir com maior facilidade o percurso vivencial (Silva et al, 2020;Da Silva et al, 2022).…”
Section: Repercussões Da Estomia Intestinal Para a Saúde Mental Da Pe...unclassified